The North Polar Spur as a Jet of Our Galaxy - Miroshnichenko, A. P. (Видавничий дім «Академперіодика», 2012)
The large-scale feature of the Galactic background radio emission, the North Polar Spur, may be a jet of our Galaxy. The jet may be enveloped in an extended cocoon with the diameter of order of the Galactic disk diameter. The estimated values of the main parameters of the jet (the magnetic field strength, the spectral index, the radio luminosity, the propagation velocity) are close to the corresponding values for the jets of weak radio galaxies. In contrast to the popular supernova remnant hypothesis, in the framework of the jet hypothesis it is possible to explain the latitudinal dependence of intensity, the magnetic field structure and the spectral index distribution in the North Polar Spur.